Analisis Postur Kerja Pekerja Gudang Barang Jadi Menggunakan Metode Ovako Work Posture Analysis System (OWAS) di PT Victorindo Kimiatama - Erna Fadilah Agustin; Rizki Achmad Darajatun (Engineering Faculty at Universitas Singaperbangsa Karawang, 2023)
PT Victorindo Kimiatama is a company engaged in the paint industry. Work activities in this company are dominantly carried out manually using human labor, one of which is in the work process in the finished goods warehouse. In manual material handling activities in the finished goods warehouse, workers often do work with bending, squatting, and rotating work posture and the process is carried out manually repeatedly with a load of up to 20 kg. So that it can pose a risk of musculoskeletal disorders. This study aims to analyze work posture finished goods warehouse workers using the Ovako Work Posture Analysis System method. Based on the results of the analysis it is known that there are four activities that are in category 3 or high category where the work conditions require renewal as soon as possible while one activity is in category 2 or medium category, which means there is a possibility of musculoskeletal risk. To minimize the emergence of musculoskeletal disorders, the suggested improvements are changes in movement or work position and designing supporting facilities that are in accordance with the worker’s body dimensions.